The Important Role Of Artificial Intelligence Technology Regulation In Protecting The Public Interest - Francisca Romana Nanik Alfiani (Journal of Social Research, 2024)
Artificial intelligence provides both good and bad. For this reason, artificial intelligence must be regulated to protect the public interest. The results of the study show that regulating artificial intelligence is not easy, very complicated, there are many challenges, moreover the development of artificial intelligence technology is very rapid while the law is slow to anticipate it. In 2022, globally there have been 37 regulations regulating artificial intelligence. From the results of the comparison of various best practices and regulations of other countries that are at the forefront in the field of artificial intelligence, such as the European Union, China, and the United States framework approach, it can be an input for the development of artificial intelligence regulations in Indonesia that ensure the responsible use of artificial intelligence, respect human values, and do not hinder the creation of an artificial intelligence development ecosystem.